Analisis manajemen pembinaan club tibra banua aquatik - Simanjuntak, Mega Sarmauli; Rachman, Aryadi; Nurdiansyah, Nurdiansyah (Jurnal Porkes, 2024)
The purpose of the study was to examine the management of coaching athletes club tibra banua aquatic. The population determination is the club management and athletes, for purposive sampling testing selected with the club owner, 2 coaches and 2 athletes. Qualitative descriptive approach method. Instruments and data collection techniques through observation, interviews, documentation and triangulation techniques. After the data is collected, it is reduced and then analyzed. The results show that the tibra banua aquatic club has implemented the management function correctly, the planning of the tibra banua aquatic club is quite good. Evidenced by the running of daily activity management and training which is held regularly according to a predetermined schedule, the tibra banua aquatics club already has an organizational structure, supervision at the tibra banua aquatics club is directly supervised by the club's chief coach and assisted by assistant coaches, for beginners directly supervised by assistant coaches and chief coaches and senior athletes supervised by the chief coach, supervision is carried out openly. For funding there is no sponsor, and only from monthly athlete fees and other service fees, club funds for the needs of tibra banua aquatic club activities. In conclusion, the club is an organization that has been registered with the parent sport, namely the Indonesian aquatic federation, so the club is said to be a legal organization and can take part in competitions held by the parent sport.